2023
DOI: 10.52880/sagakaderg.1179811
|View full text |Cite
|
Sign up to set email alerts
|

İnmeli Hastalara Bakım Verenlerde Bakım Yükü, Anksiyete ve Depresyon Düzeyinin İncelenmesi

Abstract: Giriş ve Amaç: Araştırmanın amacı inmeli hastalara bakım verenlerde bakım yükü, anksiyete ve depresyon düzeyinin incelenmesidir. Gereç ve Yöntem: Araştırmanın verileri 150 inmeli hastalara bakım verenler ile yapılmış olup Mayıs-Aralık 2020 tarihleri arasında yürütülmüştür. Veriler; Bakım veren bilgi formu, Beck Depresyon, Beck Anksiyete Ölçeği, Bakım Verme Yükü Ölçeği, Lawton ve Brody’nin Enstrümental Günlük Yaşam Aktiviteleri ve Katz’ın Günlük Yaşam Aktiviteleri Ölçeği ile toplanmış olup tanımlayıcı-kesitsel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…27 Our results were similar to previous reports showing no difference in altruism among volunteers caring for cancer patients. [26][27][28] Caregivers play essential roles as communicators and help to maintain patients' health conditions. Common problems are related to a lack of knowledge about strokes and a lack of attention from the family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Our results were similar to previous reports showing no difference in altruism among volunteers caring for cancer patients. [26][27][28] Caregivers play essential roles as communicators and help to maintain patients' health conditions. Common problems are related to a lack of knowledge about strokes and a lack of attention from the family.…”
Section: Discussionmentioning
confidence: 99%
“…When the national literature was reviewed, many studies were found to be conducted with caregivers of stroke patients, but no study was found on the altruistic behaviors of caregivers. 25,26 Although no studies were found on the altruism levels of caregivers of stroke patients in the international literature, studies conducted with caregivers in different fields were detected. 27 Our results were similar to previous reports showing no difference in altruism among volunteers caring for cancer patients.…”
Section: Discussionmentioning
confidence: 99%